Towards a cultural science of videogames: evolutionary social learning - Banks John; Potts Jason (Cultural Science)
This paper outlines a cultural science approach to videogames. Using the example of the independently developed Minecraft, we examine the dimensions of social learning involved in playing videogames that are characterised by relatively unscripted gaming environments. We argue that a cultural science approach offers an analytic framework grounded in evolutionary externalism, social learning and emergent institutions. We develop this framework by proposing a multiple games model of social learning.